PERANAN OMBUDSMAN DALAM MEWUJUDKAN GOOD GOVERNANCE DI INDONESIA - Galang Asmara (Perspektif, 2002)
Ombudsman institutions Formed on March 10,2000,by former President KH Abdurachman Wahid, has particular meaning, especially in achieving good governance. As a community control institution, it has the function to accomodate community complaint regarding government policy as well as an authority to give recommendation to government. It is expected to be avehicle to achieve accountable, transparent, and effective governance.